TOWARDS A SECURED DESIGN METHODOLOGY FOR CLOUD BASED BIOINFORMATICS APPLICATIONS - A. Nasir; M. U. G. Khan (Journal of Animal and Plant Sciences, 2015)
The amount of molecular biology data currently being generated from the lab based testing and conventional computing techniques was not thought before. But at the same time the existing techniques remains incapable to cater this massive amount data sets to retrieve meaningful results in an efficient manner. With the exponential growth of computing applications and their corresponding users, many evolutionary systems have appeared in the current markets, such as cloud computing, grid computing, bioinformatics, and video surveillance systems. Though the discovery of such systems has brought fruitful changes in daily lives of their users, there are several severe problems associated with such computing environments and security is one of the most critical issues faced by the users and service providers of these applications. These security issues and problems may arise during the life span of any evolutionary domain i.e. they are dynamic in nature as they arise and need to be handled during their life span. In this paper, we have introduced a secured methodology for designing evolutionary computing applications. We further present a working system from bioinformatics domain for testing and evaluation of the proposed design methodology.
Keywords: Cloud Computing; Bioinformatics; Evolutionary System; Secured Design Methodology; Software Engineering; Software Designs